2020
DOI: 10.4308/hjb.27.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Biological Conservation of Molluscs Based on Spatial and Temporal Distribution in Tropical Tidal Lake, Medan-Indonesia

Abstract: The tidal lake ecosystem is formed by the flow of the Belmera River and seawater through a tidal process along a course of 12 km from Belawan (Malacca Strait). This lake has a tidal lake that has the characteristics of fresh water to brackish water and Mollusc communities from freshwater species to brackish water species. This study was performed to develop a mollusc conservation strategy based on the spatial and temporal distribution of Mollusca in the tides. The study was conducted from September 2018-August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Results Based on the research of Yulianda et al (2020) on the distribution of mollusks and their conservation strategy in Lake Siombak shows the need for a zoning system consisting of a core zone and a utilization zone (Figure 8). This zoning can also be applied to the protection of shrimp and crabs in Lake Siombak.…”
Section: Discussionmentioning
confidence: 99%
“…Results Based on the research of Yulianda et al (2020) on the distribution of mollusks and their conservation strategy in Lake Siombak shows the need for a zoning system consisting of a core zone and a utilization zone (Figure 8). This zoning can also be applied to the protection of shrimp and crabs in Lake Siombak.…”
Section: Discussionmentioning
confidence: 99%
“…Some mangroves develop around the lake's perimeter [3,4]. The aquatic biota of Siombak Lake consists of groups of freshwater fish, brackish, and marine creatures [5][6][7][8]. Siombak Lake serves as catchment area for water, a flood control zone, a fishing area for fish, shellfish, and crabs, and a tourist attraction.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies of Siombak Lake have been conducted, including on morphology and hydrodynamics as well as the status and profile of lake water quality [1,2,10,11]. Studies on aquatic biodiversity such as fish, crustaceans, mollusks, and plankton have also been conducted [3][4][5][6][7][8]. In addition, studies on mangroves and bird and mammal biodiversity have been reported in 2020 and 2021 [3,12].…”
Section: Introductionmentioning
confidence: 99%
“…Mangrove trees grow on various sides of the lake border, such as Nipa Palm, Mangrove Apple, and other mangroves (Muhtadi et al 2020b). Other aquatic organisms in this lake include crabs, shrimp, snails, and fish (Leidonald et al 2019;Muhtadi et al 2022;Yulianda et al 2020). This lake has an area of 29 ha with an average depth when the mean sea level is 1.12 during the rainy season and 1.10 during the dry season (Muhtadi et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Lake Siombak is a flooded ecosystem (lotic system) and is directly connected to the coast and ocean so that it is the estuary (coastal lagoon), which is the habitat for various flora and fauna (Leidonald et al 2019;Muhtadi et al 2020bMuhtadi et al , 2020cMuhtadi et al , 2021Muhtadi et al , 2022Yulianda et al 2020). Ecologically, coastal lagoon acts as a life support system for various aquatic organisms and terrestrial organisms (Djihouessi et al 2019;Gbaguidi et al 2016) on the coast as a feeding ground, nursery ground and as spawning ground (Baptista et al 2019;Berkström et al 2020;Jaxion-Harm and Speight 2016;Lett et al 2019;Ocana-Luna and Sánchez-Ramírez 2016).…”
Section: Introductionmentioning
confidence: 99%